2021
DOI: 10.18632/aging.203255
|View full text |Cite
|
Sign up to set email alerts
|

The risk of Alzheimer’s disease according to dynamic changes in metabolic health and obesity: a nationwide population-based cohort study

Abstract: We evaluated the association of metabolic health and obesity phenotypes with the risk of Alzheimer’s disease (AD). This study enrolled 136,847 elderly participants aged 60 or above from the Korean National Health Insurance System. At baseline examinations in 2009 and 2010, subjects were categorized into four groups: the metabolically healthy non-obese (MHNO), metabolically healthy obese (MHO), metabolically unhealthy non-obese (MUNO), and metabolically unhealthy obese (MUO) groups. Based on the phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 63 publications
(76 reference statements)
1
3
0
Order By: Relevance
“…On the contrary, more recent publications report that being overweight or obese at old age protects against Alzheimer’s disease [ 120 , 121 , 122 , 123 , 124 ]. According to our nationwide population-based cohort study, the risk of AD is considerably reduced among people with MHO [ 125 ], which is consistent with some earlier findings [ 126 , 127 ]. In addition, we analyzed the risk of developing AD based on the changes in metabolic phenotype.…”
Section: Clinical Outcomes Of Mho and Possible Mechanismssupporting
confidence: 90%
“…On the contrary, more recent publications report that being overweight or obese at old age protects against Alzheimer’s disease [ 120 , 121 , 122 , 123 , 124 ]. According to our nationwide population-based cohort study, the risk of AD is considerably reduced among people with MHO [ 125 ], which is consistent with some earlier findings [ 126 , 127 ]. In addition, we analyzed the risk of developing AD based on the changes in metabolic phenotype.…”
Section: Clinical Outcomes Of Mho and Possible Mechanismssupporting
confidence: 90%
“…One of the pathophysiological features of AD was impaired cerebral glucose metabolism, which occurred long before cognitive impairment and pathological changed, and this prodromal period could last up to 10 years ( 48 50 ). Research confirmed diabetes can increase the risk of AD, and even the use of hypoglycemic drugs cannot reduce the risk ( 51 ), which can be increased two to threefold by previous study, which is not related to the risk of vascular dementia ( 52 55 ). Recombinant interferon γ the metabolic enhancement of treatment reversed the glycolytic metabolism and inflammatory functional defects of microglia, thereby alleviating the AD pathology of 5xfad mice ( 56 ).…”
Section: Discussionmentioning
confidence: 85%
“…Of these, 23 studies were excluded because the diagnosis did not meet the standardized criteria, for reasons described in Table S5. Finally, three research papers were included in this analysis [25][26][27].…”
Section: Literature Searchmentioning
confidence: 99%
“…A summary of the characteristics of the studies included is presented in Table 1 and Table S4 shows the sample sizes and incidence of dementia. The three studies were conducted in Asia and used a cohort design [25][26][27]. A total of 5,786,661 participants were included, with study population sizes from 1199 [27] to 5,669,488 [26].…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%